Spatiotemporal land use changes dynamics impacts on natural reserves in West African dryland: Drivers, carbon emissions and climate change implications - Kiribou, Issaka Abdou Razakou; Dimobe, Kangbéni; Sanou, Charles Lamoussa; Workeneh, Sintayehu Dejene (Elsevier BV, 2025)
Land use change (LUC), primarily driven by anthropogenic pressure, poses a major threat to West African drylands’ vegetation. As critical indicators of ecosystem sustainability, LUC patterns reflect how human activities alter carbon dynamics and climate vulnerability. This systematic review analyzes the spatial and temporal dynamics of LUC impacts on natural reserves. Using targeted keywords, 18 peer-reviewed articles and institutional reports were synthesized to assess LUC patterns, identify key biophysical and socio-economic drivers, and evaluate carbon and climate implications. Findings show substantial losses of natural ecosystems due to land conversion, deforestation, and soil degradation. Between 1975 and 2013, Sahelian savanna, woodland, and gallery forest declined by 23 %, 40.79 % and 23.92 %, respectively, while agricultural land, settlements, and sandy areas (Bare Soil) expanded by 91.8 %, 115 % and 49.9 %. From 2000 to 2022, 6.64 % of protected areas were converted, with the highest rates in the Gambia and Mauritania. Burkina Faso and Senegal emerged as carbon emission hotspots. These ecological shifts disrupt the regional carbon cycle and heighten climate vulnerability. Despite the pivotal role of drylands in carbon cycling, major gaps remain in monitoring and modeling LUC-related emissions. Addressing these requires improved spatial indicators, region-specific emission factors, and policy-oriented land management frameworks. Strengthening the science-policy interface is vital to ensure these indicators effectively guide sustainable land governance and climate adaptation strategies in West African drylands.